PENGGUNAAN PASAK PELEPAH SAGU SEBAGAI ALTERNATIF ALAT SAMBUNG PADA KONSTRUKSI KAYU - Sawaluddin, Risky; Picauly, Fredy; Tuanakotta, Abraham (Jurusan Teknik Sipil, 2024)
Stakes have long been known as a joint tool in wooden construction made using wood that has high shear and bending resistance, because hardwood is starting to be scarce, so this test is carried out to find other alternative materials as a substitute for wooden pegs that have high resistance, knowing how much shear strength is obtained in sago frond pegs, and the influence of pegs with variations in wood thickness on the size of the shear strength. The research method used is experimental, which is an experimental method in which an experiment is carried out to obtain information about something being experimented. This research was carried out in the Laboratory of the Department of Civil Engineering, Ambon State Polytechnic, using sago fronds as a sample in the test. The data collection technique used is experimental on test objects. The results of the shear strength test obtained on the sago frond peg at the base width of 20 mm were obtained that the average shear strength was 40,103 MPa, the width of the 30 mm base was 44,821 MPa and the width of the 40 mm base was 47,652 MPa, so it can be concluded that the shear strength is affected by the size of the support, the larger the base the greater the shear force received.